Does temporary employment increase length of commuting? Longitudinal evidence from Australia and Germany - Inga Laß; Thomas Skora; Heiko Rüger; Mark Wooden; Martin Bujard (Transportation, 2023)
On average, temporary jobs are far less stable than permanent jobs. This higher instability could potentially lower workers' incentives to relocate towards the workplace, thereby resulting in longer commutes. However, surprisingly few studies have investigated the link between temporary employment and commuting length. Building on the notion that individuals strive to optimize their utility when deciding where to work and live, we develop and test a theoretical framework that predicts commuting outcomes for different types of temporary workers – fixed-term, casual and temporary agency workers – and in different institutional contexts. We estimate fixed-effects regression models using 17 waves of data from the Household, Income and Labour Dynamics in Australia (HILDA) Survey and the German Socio-Economic Panel (SOEP). As expected, the results show that the link between temporary employment and commuting length varies by employment type and institutional context. Agency work is associated with longer commutes than permanent work in both countries, whereas this applies to fixed-term contracts for Germany only. For casual work, the findings suggest no commuting length differential to permanent employment. In terms of policy, our findings suggest lengthy commuting can be a side effect of flexible labour markets, with potentially negative implications for worker well-being, transportation management and the environment.
Keywords: 380; Work-related spatial mobility; Fixed-term contracts; Casual work; Temporary agency work; HILDA Survey; SOEP